Inoculation Timing Effect on Biological Nitrogen Fixation and Soybean Productivity - M. A. Secchi; A. R. Torres; L. H. Moro Rosso; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2019)
Soybean [Glycine max(L.) Merr.], as other legume species, has the characteristic of fixing nitrogen (N) from the atmosphere via the biological N fixation (BNF) process. When a proper symbiosis relationship between soybeans and specific bacteria has been established, the plants can obtain up to 98% of the total N need. However, several factors can negatively affect BNF, impairing its contribution to nutrient demand and reducing crop productivity. In this scenario, additional inoculation could help the plant to overcome potential N gaps in BNF. Therefore, the goal of this project was to investigate if additional inoculation at different growth stages of the soybean growing season could increase nodulation, improve BNF (N contribution) and productivity of two varieties from maturity groups (MG) III and IV. To address this objective, different strategies for N supply were tested in a greenhouse and two field locations (Ashland Bottoms and Ottawa, KS) during the 2018 growing season. Trials were arranged in a complete randomized block design with four replications. The main outcomes of this study were that nodulation (total number of nodules per plant), plant dry biomass, relative abundance of ureide (RAU (%), indirect measurement of BNF), and productivity did not differ between inoculated treatments.
Keywords: Glycine max; inoculant; rhizobia